Communication management in a millennium of chaos and change - Ursula Stroh (Communicare)
Changes occur in organisations because of changes in the environment. Conflicts arise between the organisation and internal and external stakeholders of the organisation because of these uncontrolled influences. Small points of disorder may easily escalate into disordered crises and chaos (bifurcations and the butterfly effect). Communication management - and specifically constructive conflict management - could lead to 'positive chaos' and a culture (strange attractor) of constant change. Positive chaos implies an unstable, seemingly disordered situation that could bring about productive, creative, and improved results. Communication management could be used by organisations to reorganise themselves out of disorder and chaos by facilitating conflicts and diversity. Strategic planning will become even more important, but will have to change from the basic premise of control and prediction to scenario planning, and the emphasis will be on relationship building.